2016
DOI: 10.1002/ana.24614
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and signatures of recovery from neglect in acute stroke

Abstract: System excitability and early recruitment of contralesional functional homologues represented specific features of favorable recovery in acute stroke. In severe strokes leading to neglect, contralesional functional homologues support recovery by modulating the preserved ipsilesional network, and initial functional connectivity between them might predict recovery course and help to identify patients with potentially poor recovery requiring more intensive early rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 76 publications
(194 reference statements)
5
38
0
Order By: Relevance
“…However, the effects of this stimulation present with a considerable interindividual variability (Lefaucheur et al, 2014), which is scarcely understood. According to recent findings (Umarova et al, 2016), the role of the contralesional hemisphere in neglect could be compensatory, rendering its inhibitory stimulation even detrimental. Moreover, recent accounts postulate that the recovery of stroke in general, and of neglect in particular, would follow !…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the effects of this stimulation present with a considerable interindividual variability (Lefaucheur et al, 2014), which is scarcely understood. According to recent findings (Umarova et al, 2016), the role of the contralesional hemisphere in neglect could be compensatory, rendering its inhibitory stimulation even detrimental. Moreover, recent accounts postulate that the recovery of stroke in general, and of neglect in particular, would follow !…”
Section: Discussionmentioning
confidence: 97%
“…However, on an individual level, a conspicuous variability in the effects of contralesional, inhibitory NIBS in neglect has been observed, i.e., not all patients equally benefit from this approach (Lefaucheur et al, 2014). Conversely, and somewhat in line with this variability, some studies point to a compensatory role of the contralesional, undamaged hemisphere (Lunven et al, 2015;Umarova et al, 2016), suggesting that its activity should be facilitated rather than inhibited. Finally, in a third perspective, other recent studies have suggested that neglect recovery dynamics after stroke follow fixed, non-influenceable patterns: within three months after stroke, patients would recover ≈70% of their initial impairment, irrespectively of the type of applied therapeutic approaches (i.e., the so-called Proportional recovery rule, (Marchi et al, 2017;Ramsey et al, 2017;Winters et al, 2017)).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from perfusion, there is important clinical implications for the estimation of the function of the brain in the poststroke phase. rs‐fMRI is an imaging technique that can estimate brain function noninvasively and has been used increasingly more for functional recovery assessment in stroke patients . In this study we applied three rs‐fMRI measurements: FC, ALFF, and ReHo, to assess the functional recovery of AIS patients after reperfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…rs-fMRI is an imaging technique that can estimate brain function noninvasively and has been used increasingly more for functional recovery assessment in stroke patients. [24][25][26] In this study we applied three rs-fMRI measurements: FC, ALFF, and ReHo, to assess the functional recovery of AIS patients after reperfusion therapy. To the best of our knowledge, a voxelwise analysis of the functional status of the brain using rs-fMRI has not been conducted in AIS patients after reperfusion treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal fMRI study revealed different signatures: a favorable course of recovery was specifically associated with increased activation in essential functional nodes, when the left prefrontal region replaces the irreversibly damaged ventral attention system and supports spatial performance, driving the preserved ipsilesional dorsal attention system. The strength of functional connectivity between right parietal and left prefrontal region might predict the course of recovery [119. ]…”
Section: Structural Imagingmentioning
confidence: 99%